Analyzing the perception of happiness among Korean medical students using a concept mapping methodology: a cross-sectional study - Lee, Jaemu; Park, Kyung Hye; Lee, Sangmi Teresa (Frontiers in Public Health, 2025)
IntroductionHappiness differs according to population groups and cultures. For medical students, more studies have focused on negative emotions than on happiness. This study explored the overall perceptions and standards of medical students to analyze the concept of happiness from various perspectives in the Korean context.MethodsA concept mapping analysis comprising five stages was conducted with medical students at Yonsei University’s Wonju College of Medicine in South Korea. Focus questions were generated in Phase 1, and 23 students participated in individual brainstorming in Phase 2. Fifty statements were confirmed in Phase 3. Sixteen students assigned an importance score to each statement and participated in the individual sorting of statements and naming of categories in Phase 4. Finally, the concept maps were interpreted using multidimensional scaling and hierarchical cluster analysis.ResultsThe medical students’ perception of happiness was divided into two dimensions, “Study–Life” on the X-axis and “Self–Relationship” on the Y-axis, and was expressed in three categories and five sub-categories. The subcategories of “Self-management” and “Quality of life” were grouped under “Personal development,” “Social support” was named as a single category, and “Guaranteed future” and “Academic achievement” were grouped as “Professional fulfillment.” The most important sub-category for medical students was “Social support.” Among the statements generated in these categories, the most important was “When I have a healthy body and stamina,” which belonged to “Quality of life.”DiscussionThis study showed that to enhance the happiness of medical students, a system that supports their social relationships, careers, learning, and individual efforts is required. The results of this study can provide information for the development of student support programs that allow medical educators and institutions to promote medical students’ happiness.